Clinical Practice Guidelines for Cardiogenic Shock. - Arelys Falcón Hernández; Victor René Navarro Machado (Medisur)
Clinical Practice Guidelines for Cardiogenic Shock. It has been defined as the persistence of tissue hypoperfusion, usually associated to blood hypotension as the result of heart pumping failure. This document includes a review of the main aspects as concepts, aetiology, diagnosis and treatment. It includes the concept, risk factors, clinical presentations, diagnosis, and therapy based on the possibilities of our environment. It includes assessment guidelines focused on the most important aspects to be accomplished.